Pelatihan Pengembangan Modul Ajar Berbasis Implementasi Kurikulum Merdeka bagi Guru Sekolah Dasar di Kecamatan Bantur Kabupaten Malang: Training on the Development of Teaching Modules Based on the Implementation of the "Merdeka" Curriculum for Elementary School Teachers in Bantur District, Malang Regency - Sumarsono, Raden Bambang; Rochmawati, Rochmawati; Zulkarnain, Wildan; Prestiadi, Dedi; Ubaidilah, Endra; Bhayangkara, Athalla Nauval; Indrawanto, Dwi Wahyu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Community service activities with the theme of training in developing teaching modules based on the implementation of the "Merdeka" curriculum for elementary school teachers in the Bantur District, Malang Regency. The objectives of this activity are to assist teachers in developing teaching modules based on the implementation of the "Merdeka" curriculum, to assess the performance level of the resource persons, and to assess the performance level of the organizing committee. The community service activities were conducted through several methods including lectures, discussions, Q&A sessions, modeling, demonstrations, Problem-Based Learning (PBL), and assignments. Participants consisted of 103 teachers from grades 2 and 5. Supporting instruments for this community service include pre-test and post-test sheets, and program evaluation questionnaires. The training material covers the implementation of the "Merdeka" curriculum, characteristics of learning in the "Merdeka" curriculum, and the development of assessment instruments for student learning outcomes. The results of this training indicate a 35.7% improvement in teachers' ability to develop teaching modules, 56.31% performance level of the resource persons in assisting participants categorized as good, and 74.76% performance level of the organizing committee categorized as very good.